THE ANALYSIS OF FACTORS WHICH INFLUENCE THE MANAGERIAL AND INSTITUTIONAL OWNERSHIP ON BASIC INDUSTRY AND CHEMICAL SECTORS AT INDONESIA STOCK EXCHANGE 2010 - 2014 - Andrena Novita Santoso; Werner R. Murhadi; Endang Ernawati (Journal of Management and Business, 2015)
The purpose of this study is to determine the effect of the following corporation’s variables: value, size, debt policy, growth, liquidity, dividend policy on managerial and  institutional ownership in the base and chemical industry sector listed on the Indonesia stock exchange during 2010 through 2014. The findings showed that: (i) Corporation’s value and size variables have significant negative effect on managerial ownership; liquidity variable has significant positive effect on managerial ownership. On the other hand, debt policy, growth and dividend policy variables have non-significant negative effect on managerial ownership. (ii) Corporation’s value and size variables have significant positive effect on institutional ownership; debt policy variable has significant negative effect on institutional ownership, while growth, liquidity and dividend policy variables have non-significant positive effect on institutional ownership.